Molecular Ecology of New World Quails: Messages for Managers - Damon Williford; Randy W. DeYoung; Leonard A. Brennan (National Quail Symposium Proceedings, 2017)
Recent genetic studies of New World quails (Odontophoridae) have yielded important, and sometimes, counter-intuitive insights regarding their evolutionary relationships, genetic diversity, population structure, and biogeographic history. Many of these new insights have important implications for managers. New World quails are a distinct family within galliforms, most closely related to guineafowl (Numididae) and pheasants (Phasianidae) rather than guans and chachalacas (Cracidae). The African stone partridges (Ptilopachus spp.) are the closest living relatives of the New World quails. The combination of phylogeographic studies with ecological niche modeling has revealed the biogeographic history of several species of New World quails, including Pleistocene refugia and post-Pleistocene range expansions, contractions, or stasis. Divergence times within and among genera often date to climactic or geologic events 1–5 million years ago. The many subspecies of quail described over the past 100 years were based on minor differences in plumage and probably represent artificial sectioning of latitudinal clines rather than historically isolated and evolutionary distinct units. Subspecies are often used as proxies for management units, but conservation efforts directed at the northern bobwhite (Colinus virginianus) and scaled (Callipepla squamata), California (C. californica), and Gambel’s (C. gambelii) quails may not benefit from such an approach. Ecological regions, rather than subspecies, are probably more appropriate as a ‘‘management unit.’’ The overall lack of population structure, evidence of long-distance dispersal and historical gene flow among populations, and the cyclical population dynamics of these species suggest that there is a biological basis for conserving large blocks of interconnected habitat. Focal areas of restoration projects should be spatially extensive and interconnected to facilitate dispersal and recolonization. With a better understanding of how quail populations responded to past climactic conditions, we are better able to predict how quail may respond to future conditions and ensure the conservation of these iconic New World birds.
Keywords: landscape genetics; New World quails; Odontophoridae; phylogenetics; phylogeography; population genetics; taxonomy